A real-time software-defined networking framework for cyber-physical production systems - Silva, Luís Emanuel Moutinho da (2020)
Emerging concepts such as Smart Production, Industrial Internet of Things, and Industry 4.0 bring a radically new set of requirements to the way industrial systems are engineered. In what concerns the communication infrastructure, support to dynamic environments, interoperability and heterogeneity, combined with a significant increase in the number of devices, are just a few of the challenges that must be faced. Software-defined networking (SDN) is a disruptive networking paradigm that emerged on campus networks but soon captured considerable interest from industry and academia, and is considered a leap forward in open traffic management. It exhibits two particular features that are very well suited to manage a network with real-time requirements: (i) a centralized resource control, completely decoupled from the data plane, and (ii), a fine granular resource control, down to validating each single frame received in each port of a switch. However, due to its roots, the SDN traffic model favors the average network throughput with best-effort policies, eventually imposing bandwidth constraints or setting fixed priorities. This model is not compatible with industrial scenarios, which typically have strict requirements in terms of predictability, timeliness and fault tolerance. This dissertation supports the thesis that is possible to support the flexibility, timeliness, and heterogeneity requirements of emerging industrial applications by enhancing SDN technologies with the means to enact resource reservations on networks comprising switching platforms with component-based real-time services. In particular, this work: (i) enhances a real-time switching platform with SDN services, (ii) develops extensions to OpenFlow, a seminal SDN protocol, so an OpenFlow controller may be able to configure both SDN and real-time services, and (iii) extends an OpenFlow controller with scheduling analysis so it may perform the admission control of new traffic flows while maintaining the timeliness behavior of the whole network. A prototype of the proposed real-time SDN framework is used to perform several experiments that validate the desired properties and consequently, the thesis.